2006
DOI: 10.1177/1748895806060665
|View full text |Cite
|
Sign up to set email alerts
|

How the resettlement of prisoners promotes desistance from crime

Abstract: The article considers current developments in the 'resettlement' of prisoners in the light of recent theory and research on factors promoting desistance from crime. While recognizing improvements promised by the Reducing Re-offending National Action Plan and the concept of 'end-to-end' offender management, it is argued that these are unlikely to reduce re-offending significantly without greater attention to individual offenders' mental processes and levels of selfmotivation, which are identified by the desista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 17 publications
2
118
0
Order By: Relevance
“…McNeill, 2006;Maruna & LeBel, 2010) and other similar approaches that seek to promote "good lives" (Ward, 2010) by focusing on things which might make offenders" lives meaningful and fostering the changes that offenders make for themselves as they mature. Maguire and Raynor (2006) identify an increasing convergence between effective resettlement practice and the desistance literature, although their advocacy of an approach that addresses both opportunities and thinking may have more limited relevance to women. This is not to suggest that women who offend never make inappropriate choices with respect to their decisions to offend but their decisionmaking needs to be understood in the context of severely constrained choices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McNeill, 2006;Maruna & LeBel, 2010) and other similar approaches that seek to promote "good lives" (Ward, 2010) by focusing on things which might make offenders" lives meaningful and fostering the changes that offenders make for themselves as they mature. Maguire and Raynor (2006) identify an increasing convergence between effective resettlement practice and the desistance literature, although their advocacy of an approach that addresses both opportunities and thinking may have more limited relevance to women. This is not to suggest that women who offend never make inappropriate choices with respect to their decisions to offend but their decisionmaking needs to be understood in the context of severely constrained choices.…”
Section: Discussionmentioning
confidence: 99%
“…16 Maguire and Raynor (2006) have suggested that ex-prisoners" lack of access to social justice may reflect both a lack of access to resources and the absence of commitment on the part of society to prisoner resettlement. However they also argue that strengths-based approaches, by focusing on the potential for offenders to contribute positively to society, perhaps offer greater hope of public acceptance and effectiveness of ex-prisoner re-integration.…”
mentioning
confidence: 99%
“…Drawing on the desistance studies cited above, and many others, a body of scholarship has emerged which, following Farrall's (2002) injunction that practice should become 'desistance-focused', seeks to interpret desistance research for practice (for example, see Maguire and Raynor, 2006;McCulloch and McNeill, 2008;McNeill, 2003McNeill, , 2006McNeill, , 2009bMcNeill and Weaver, 2010;Porporino 2010;Weaver and McNeill, 2010). This work tends to stress (albeit to varying degrees) seven central themes:…”
Section: Going With the Grainmentioning
confidence: 99%
“…The empirical base on which their theorizing rests is typically but not exclusively qualitative in-depth interviews carried out with ex-offenders (eg Laub and Sampson, 2001;Farrall, 2002Farrall, , 2006Maguire and Raynor, 2006;McNeill, 2006McNeill, , 2007LeBel et al, 2008). This body of work stresses the importance of understanding the centrality of offenders' agency (or capacity to exert control over their lives) in deciding to stop offending, and to appreciate that criminal justice agencies are only one of the many factors that impinge on offenders.…”
Section: Desistance Studiesmentioning
confidence: 99%